STRATEGI PENGEMBANGAN LAYANAN BERBASIS DIGITAL DALAM MENINGKATKAN KEPUASAN ANGGOTA DI KOPERASI CU (CREDIT UNION) BETANG ASI PALANGKA RAYA: Digital-Based Service Development Strategy To Improve Member Satisfaction At The Betang Asi Credit Union Cooperative In Palangka Raya - Hariansano, Hendry Wahyu; Uda, Tonich; Lenlioni, Liling (Ganec Swara, 2026)
This study aims to analyze the digital-based service development strategy to increase member satisfaction at the Betang Asi Credit Union Cooperative, Palangka Raya. Developments in information technology encourage financial institutions, including cooperatives, to adapt by providing more effective, efficient, and easily accessible digital services to members. This study uses a qualitative approach with descriptive methods to describe the cooperative's strategies in developing digital services and their impact on member satisfaction. Data collection techniques were conducted through interviews, observation, and documentation. The research results show that the development of digital services such as mobile applications, online transaction services, and member information systems can improve ease of service access, accelerate transaction processes, and enhance member convenience in interacting with the cooperative. However, several challenges remain, such as varying levels of digital literacy among members and limited technological infrastructure. Therefore, further strategies are needed, such as increasing the socialization of digital service usage, training for members, and strengthening information technology systems to improve the quality of cooperative services. With optimal digital service development, it is hoped that member satisfaction at the Betang Asi Palangka Raya Credit Union Cooperative will continue to increase.